Admiral Cheng Ho and the Islamization of Sundanese Society: A Maritime Legacy - M. Kautsar Thariq Syah; Putri Lailatus Sa’adah; Supi Septia Wahyuni; Teddiansyah Nata Negara; Nurcahya, Yan (JURNAL JAWI, 2025)
This study aims to examine the role of Admiral Zheng He's maritime expeditions in the process of Islamization in the Sunda region, specifically how interactions between the Chinese Muslim community and local communities contributed to socio-religious change during the transition from Hinduism and Buddhism to Islam. This study was conducted because the role of Chinese Muslims in the history of Islam in the Indonesian archipelago has received little attention in mainstream literature. The study uses a qualitative analytical approach through historical sources, including local manuscripts, dynastic chronicles, travel notes, and archaeological data related to the missionary activities of scholars who arrived with Zheng He's fleet. The results show that Zheng He's expeditions were not only political and economic missions, but also important vehicles for the spread of Islam in the Sunda region. Figures such as Sheikh Hasanuddin (Sheikh Quro) and Sheikh Nurjati played a central role in establishing early Islamic educational institutions, including Pondok Quro, which later became centers of missionary work in Karawang and Cirebon. Intense interactions between Chinese Muslims and local communities accelerated cultural and religious transformation, demonstrating that Islamization in the Sunda region was a multi-ethnic process connected by international maritime networks. The implications of this research emphasize the need to strengthen maritime history research to understand the contribution of sea routes to the spread of Islam, as well as to encourage the preservation of Chinese Muslim historical sites as sources of public education. These findings also encourage the integration of multiethnic narratives into history curricula and the strengthening of Indonesia-China research collaborations in Islamic history studies. The originality of this research lies in its comprehensive explanation of the relationship between Zheng He's expeditions, the arrival of Chinese Muslim scholars, and early Islamic educational institutions—a perspective rarely explored in previous research.